Determinan Pemilihan Karier dalam Bidang Akuntansi Pemerintahan: Studi Empiris Mahasiswa Akuntansi di Padang - Regina, Henny Julia; Fauzihardani, Eka (Jurnal Nuansa Karya Akuntansi, 2023)
The objective of this research was to examine the direct effect and indirect effect of the independent variables (influence of the third parties, anticipated conflict, and impostor syndrome) on the dependent variable (career selection in government accounting) through the intervening/mediating variable (career self-efficacy). The novelty of this research is combining SCCT and TPB by taking one component of those theories. To determine the sample, this research uses proportionate stratified random sampling. The respondents in this research were undergraduate accounting students force of 2018 to 2019 which is in 4 universities in Padang City (UNP, UNAND, UBH, and UPI) as many as 75 respondents. The data collection method used is a self-administered survey. The data in this research were analyzed using Partial Least Square (PLS). The research findings indicated that the influence of the third parties has a positive significant effect on career selection in government accounting. The anticipated conflict has a negative significant effect on career selection in government accounting. Impostor syndrome has no significant effect on career selection in government accounting. Meanwhile, the influence of the third parties, anticipated conflict, and impostor syndrome mediated by career-self efficacy have no significant effect on career selection in government accounting.